The role of emotional intelligence, depression, and anger as mediators in the relationship between cyberbullying and life satisfaction among youth in Selangor, Malaysia - Ma’rof, Aini Azeqa; Abdullah, Haslinda; Dahamat Azam, Mohammad Naqiuddin (Human Resource Management Academic Research Society, 2024)
This study investigates the mediating roles of emotional intelligence, depression, and anger in the relationship between cyberbullying and life satisfaction among youth in Selangor, Malaysia. Utilizing a cross-sectional survey of 442 students from Malaysian public universities, the research employs established instruments to measure cyberbullying, emotional intelligence, depression, anger, and life satisfaction. The findings reveal that cyberbullying significantly predicts reduced life satisfaction, with emotional intelligence, depression, and anger serving as crucial mediators. Students experiencing higher levels of cyberbullying report greater emotional distress, lower emotional intelligence, and higher levels of depression and anger, which in turn, adversely affect their life satisfaction. These results underscore the importance of addressing both emotional regulation and mental health in interventions aimed at improving life satisfaction among youth. Practical strategies suggested including implementing emotional intelligence training programs, providing mental health support, and fostering anger management skills. This study provides empirical evidence on the mediating roles of emotional intelligence, depression, and anger in the relationship between cyberbullying and life satisfaction. By understanding these dynamics, educators and mental health professionals can develop targeted strategies to support youth in managing the effects of cyberbullying and enhancing life satisfaction, ultimately improving their overall wellbeing. These findings offer valuable insights for both academics and practitioners in the fields of mental health and educational intervention.